Milosz and the Problem of Evil - Tischner, Łukasz, 1968- (Book collections on Project MUSE., 2015)
While scholars have chronicled Czesław Miłosz's engagement with religious belief, no previous book-length treatment has focused on his struggles with theodicy in both poetry and thought. Miłosz wrestled with the problem of believing in a just God given the powerful evidence to the contrary in the natural world as he observed it and in the horrors of World War II and its aftermath in Poland. Rather than attempt to survey Miłosz's vast oeuvre, Łukasz Tischner focuses on several key works--The Land of Ulro, The World, The Issa Valley, A Treatise on Morals, A Treatise on Poetry, and From the Rising of the Sun--carefully tracing the development of Miłosz's moral arguments, especially in relation to the key texts that influenced him, among them the Bible, the Gnostic writings, and the works of Blake, Hegel, Kierkegaard, and Schopenhauer. The result is a book that examines Miłosz as both a thinker and an artist, shedding new light on all aspects of his oeuvre.